(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
Blended learning, a pedagogical approach that integrates traditional face-to-face instruction with online digital components, has become a powerful strategy for enhancing teacher education. This article explores how blended learning contributes to developing the professional competence of future English teachers in Uzbekistan’s higher education system. By combining theoretical perspectives with empirical evidence, the study examines how digital tools, multimedia resources, and online collaboration platforms improve language teaching skills, digital literacy, and pedagogical innovation. The findings highlight that blended learning not only fosters student engagement and autonomy but also effectively bridges the gap between traditional and modern teaching methodologies. The paper concludes with recommendations for policymakers and educational institutions to promote continuous teacher professional development through blended learning models.